Pembuatan Media Pembelajaran Berbasis Digital untuk Guru dalam Meningkatkan Pemahaman Pendidikan Seks Siswa Sekolah Dasar - Ilham, Ilham; Fauqi, Amal; Srirahmawati, Ija; Hendriani, Nunung; Rezki, Muhammad Reza (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
Early childhood education plays an important role in equipping children with knowledge and skills for the future. One of the crucial aspects of this education is sex education, which aims to introduce students to the concept of privacy and body boundaries, as well as preventing potential sexual crimes. At SDN 31 Dompu, there are challenges in student behavior and the lack of use of digital technology in learning. The Community Service Program (PkM) carried out by STKIP Yapis Dompu aims to increase teachers' understanding and skills in using digital-based learning media, especially through making sex education posters using the Canva platform. The program implementation method includes three stages: preparation, implementation, and evaluation. In the preparation stage, surveys, outreach and preparation of training materials were carried out. Program implementation includes training and assistance in making poster learning media using Canva, as well as workshops to improve participants' skills. The evaluation stage aims to monitor the results and sustainability of the program. The results showed that 85% of participants experienced improved graphic design skills, 80% felt more confident in using Canva, and 90% felt the training deepened their understanding of presenting sex education information. This program succeeded in improving the quality of learning media at SDN 31 Dompu and created a more positive learning environment.